Rundgang 4 - 7 : Change is good, My world is not enough, Flexibilitätsversuche, German Leitkultur. - Berger, Tobias; Block, René (Kassel : Museum Fridericianum, 2001)
Abramovic, Marina & Ulay ; Aladag, Nevin ; Antille, Emmanuelle ; Aumüller, Heike ; Biava, Maura ; Brembeck, Tobias ; Budde, Nine ; candela2 ; Convex TV ; Coste, Annelise ; Crash media ; Dahlem, Björn ; Danke, Tobias & Raphael ; Hinterthür, Marcus ; Hirsch, Andreas ; Husain, Oliver ; Richter, Claus ; Jensen, Sergej ; Jankowski, Christian ; Keller, Dagmar ; Wittwer, Martin ; Krumwiede, Christiane ; Laessing, Nick ; Lück, René ; Meinzer, Dirk ; Mohammadi, Ashkan ; Museum für werdende Kunst ; Öztürk, Anny & Sibel ; Phantombüro ; Pousttchi, Bettina ; Schäfer, Marie-Celine ; Schäfer, Sandra ; Schinwald, Markus ; Schreiber, Ralf ; Sievers, Heiko ; Snyder, Sean ; Wagner, Silke ; Wehrmann, Mark ; Wermers, Nicole ; Wiedemann, Moritz ; Wieder, Axel John ; Zeh, René ; Ziegler, Ella
biog., tent. p. 58-77
Duits
Rundgang 4 - 7, Rundgang 4: Museum Fridericianum, Kassel, 24. April - 18. Juli 1999, Rundgang 5 : My world is not enough, Museum Fridericianum, Kassel, 8. April - 21. Mai 2000, Rundgang 6 : flexibilitätsversuche, Museum Fridericianum, Kassel, 11. November 2000 - 4. März 2001, Rundgang 7 : German Leitkultur, Museum Fridericianum, Kassel, 1. April - 10. Juni 2001
boek